The Impact of Verbal Bullying on Elementary School Students' Learning Motivation - Astrid Ramadhanti; Dinda Aurilia; Sari Mardiah; Dahnilsyah Dahnilsyah (JURNAL PENA EDUKASI, 2025)
Abstract: Verbal bullying is one of the factors inhibiting student learning motivation. Motivation is the foundation for students to achieve maximum learning outcomes, which in turn serve as the basis for determining the attainment of expected competencies. Therefore, it is crucial to comprehend the connection between verbal bullying and student motivation for learning. This study aims to explore the impact of verbal bullying on student learning motivation in elementary schools and provide recommendations to mitigate its negative effects on the school environment. Moreover, it creates a positive culture in schools. This study employs a qualitative research approach, utilizing the Systematic Literature Review (SLR) method. The findings indicate that verbal bullying significantly reduces elementary school students’ learning motivation by causing psychological distress, such as low self-confidence, anxiety, and social isolation. These negative effects disrupt students’ engagement in the learning process, ultimately hindering their academic performance. Early intervention and consistent anti-bullying measures are essential to prevent long-term educational setbacks. Thus, creating a supportive school environment through collaboration among educators, parents, and policy-makers can help mitigate the impact of verbal bullying and foster positive student development.Keywords: learning motivation; primary school; verbal bullying